2005
DOI: 10.1128/aac.49.6.2226-2236.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Expression Profiling of the Response to Azole, Polyene, Echinocandin, and Pyrimidine Antifungal Agents inCandida albicans

Abstract: Antifungal agents exert their activity through a variety of mechanisms, some of which are poorly understood. We examined changes in the gene expression profile of Candida albicans following exposure to representatives of the four currently available classes of antifungal agents used in the treatment of systemic fungal infections. Ketoconazole exposure increased expression of genes involved in lipid, fatty acid, and sterol metabolism, including NCP1, MCR1, CYB5, ERG2, ERG3, ERG10, ERG25, ERG251, and that encodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
267
4
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(310 citation statements)
references
References 43 publications
37
267
4
2
Order By: Relevance
“…Global gene expression studies have revealed that when C. albicans is exposed to amphotericin B, 256 genes are differentially expressed. These genes are involved primarily in protein synthesis, small-molecule transport, cell stress responses, and sterol metabolism (340). This suggests that there is a multitude of factors responsible for tolerance and resistance to polyenes besides target alteration.…”
Section: Candida Albicans Drug Resistance: the Polyenesmentioning
confidence: 99%
“…Global gene expression studies have revealed that when C. albicans is exposed to amphotericin B, 256 genes are differentially expressed. These genes are involved primarily in protein synthesis, small-molecule transport, cell stress responses, and sterol metabolism (340). This suggests that there is a multitude of factors responsible for tolerance and resistance to polyenes besides target alteration.…”
Section: Candida Albicans Drug Resistance: the Polyenesmentioning
confidence: 99%
“…The hgt4⌬/⌬ strain showed reduced the capacity to form filaments. XOG1 expression increased (1.6-fold) upon exposure to ketoconazole (transcriptional profiling [210]). The expression of a subunit of ␤-1,3-glucan synthase also increased.…”
Section: Cell Wall-localized Proteinsmentioning
confidence: 99%
“…The mechanisms of resistance to 5-FC in clinical C. albicans isolates focus on the proteins involved in pyrimidine salvage pathway and the alterations in gene expression (21,22). Mutations in the cytosine deaminase gene FCY1 (named FCA1 gene in C. albicans) or cytosine permease gene FCY2, which may result in the poor uptake of drug, are the most common causes of drug resistance (23,24).…”
Section: Discussionmentioning
confidence: 99%